CONTEMPORARY ECONOMIC DIPLOMACY OF THE PRC IN RELATIONS WITH DEVELOPING COUNTRIES (THE HORN OF AFRICA CASE) (Вісник: Міжнародні відносини, 2024)
China, since the successful implementation of the Reform and Opening-Up policy, moved away from the Marxist-Maoist approach to diplomacy towards an incrisingly integrative approach, combining the Confucian-tradition ethical messages with endeavors to incorporate the methodology and practical approaches of  Western schools of international relations and diplomacy. The author's goal was an inter-disciplinary analysis of  ideological, value and theoretical foundations, the current state and features of China's economic diplomacy  in regard to developing countries, using the case of the Horn of Africa region being a focus of the key world actors' clashing interests.